A floating piezoelectric electromagnetic hybrid wave vibration energy harvester actuated by a rotating wobble ball. (1st May 2023) - Shi, Ge; Zeng, Wentao; Xia, Yinshui; Xu, Jubing; Jia, Shengyao; Li, Qing; Wang, Xiudeng; Xia, Huakang; Ye, Yidie
Abstract: This paper presents a floating piezoelectric electromagnetic hybrid wave vibration energy harvester actuated by a rotating wobble ball. The kinematic equation of the rotating wobble ball under the influence of the wave is established by simplifying the ocean wave model. One merit of the proposed harvester is that it can harvest wave vibration energy via a frequency up-conversion mechanism. The vibration energy of a wave is converted into electrical energy by the electromagnetic generator (EMG) and the piezoelectric ceramic transducer (PZT). Low-frequency vibration energy is converted into the high frequency vibration of the PZTs using frequency up-conversion mechanism. The results show that the maximum power generated by the proposed hybrid energy harvester is 21.95 mW when the external frequency of the wave is 1.4 Hz. Additionally, two PZTs and the EMG successfully output about 11.26 mW of power to light up LEDs throughout a test of low-power electronics. The results demonstrate that low-frequency wave vibrations can be efficiently harvested using the proposed hybrid vibration energy harvester. Highlights: The harvester can harvest energy from ultra-low frequency (0.4–1.8 Hz) ocean waves. The harvester converts the heaving motion of ocean waves into the rotating motion of a rotating wobble ball. The harvester can use one excitation source to achieve piezoelectric frequency up-conversion and electromagnetic conversion. A significant power of 21.95 mW is obtained.